Web portals for information management and enhancement of the co-creational experience (2019)
Multiple strategies for a more open innovation have been put into place looking for a conjunct generation of value among different actors through the co-creation of experiences. Some are face-to-face techniques in which participants have to be focused in the same space-time scenario, while other use social media and web portals because of their potential for facilitating collaboration and co-creation naturally while also providing specialized tools according to the particular requirements of s project. This research shows a framework for the selection of a web portal for co-creation, facilitating thus the choice for the more suitable portal for a virtual open innovation process with clear criteria. On one hand, some preliminary results highlight that the adequate choice of the interaction tool in a process of open innovation is decisive for the success of the process. On the other internet is ratified (specifically, tools like business innovation portals) is an enhancer for the interchange of information because it facilitates the interaction among participants geographically scattered while at the same time offers the opportunity of asynchronous collaboration. With this feature time and space as face-to-face limitants are eliminated.